Recruiting general practice patients for large clinical trials: lessons from the Aspirin in Reducing Events in the Elderly (ASPREE) study. Issue 4 (21st December 2018) - Lockery, Jessica E; Collyer, Taya A; Abhayaratna, Walter P; Fitzgerald, Sharyn M; McNeil, John J; Nelson, Mark R; Orchard, Suzanne G; Reid, Christopher; Stocks, Nigel P; Trevaks, Ruth E; Woods, Robyn
Abstract: Objective: To assess the factors that contributed to the successful completion of recruitment for the largest clinical trial ever conducted in Australia, the Aspirin in Reducing Events in the Elderly (ASPREE) study. Design: Enrolment of GPs; identification of potential participants in general practice databases; screening of participants. Setting, participants: Selected general practices across southeast Australia (Tasmania, Victoria, Australian Capital Territory, New South Wales, South Australia). Major outcomes: Numbers of patients per GP screened and randomised to participation; geographic and demographic factors that influenced screening and randomising of patients. Results: 2717 of 5833 GPs approached (47%) enrolled to recruit patients for the study; 2053 (76%) recruited at least one randomised participant. The highest randomised participant rate per GP was for Tasmania (median, 5; IQR, 1–11), driven by the high rate of participant inclusion at phone screening. GPs in inner regional (adjusted odds ratio [aOR], 1.45; 95% CI, 1.14–1.84) and outer regional areas (aOR, 1.86; 95% CI, 1.19–2.88) were more likely than GPs in major cities to recruit at least one randomised participant. GPs in areas with a high proportion of people aged 70 years or more were more likely to randomise at least one participant (per percentage point increase: aOR, 1.10; 95% CI, 1.05–1.15). The number of randomised patients declined with time from GP enrolment to first randomisation. Conclusion: General practice can be a rich environment for research when barriers to recruitment are overcome. Including regional GPs and focusing efforts in areas with the highest proportions of potentially eligible participants improves recruitment. The success of ASPREE attests to the clinical importance of its research question for Australian GPs.